2014
DOI: 10.1007/s11262-014-1102-8
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the hemagglutinin gene of H3N8 canine influenza virus in dogs

Abstract: With the widespread use of a recently developed canine influenza virus (CIV) H3N8 vaccine, continual molecular evaluation of circulating CIVs is necessary for monitoring antigenic drift. The aim of this project was to further describe the genetic evolution of CIV, as well as determine any genetic variation within potential antigenic regions that might result in antigenic drift. To this end, the hemagglutinin gene of 19 CIV isolates from dogs residing in Colorado, New York, and South Carolina humane shelters wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Furthermore, recent analyses of the amino acid sequence from emerging and contemporary CIV-H3N8 isolates, revealed that significant antigenic drift may have occurred. Altogether since its introduction into the canine population, evolution dynamics studies of CIV-H3N8 suggested that it evolved and diverged into multiple lineages (81).…”
Section: Equine Interspecies Transmissionmentioning
confidence: 99%
“…Furthermore, recent analyses of the amino acid sequence from emerging and contemporary CIV-H3N8 isolates, revealed that significant antigenic drift may have occurred. Altogether since its introduction into the canine population, evolution dynamics studies of CIV-H3N8 suggested that it evolved and diverged into multiple lineages (81).…”
Section: Equine Interspecies Transmissionmentioning
confidence: 99%
“…In light of phylogenetic analysis, the CIVs have formed two distinct lineage groups within the IAVs over the last decade—an Asian H3N2 avian-origin lineage and a North American H3N8 equine-origin lineage– as a result of a direct interspecies transmission from different hosts [ 8 11 ]. For this reason, the H3N2 CIVs have shown low levels of genetic diversity in the distinct lineage group belonging to the Eurasian avian lineages [ 10 20 ]; similarly, H3N8 CIVs have formed a single monophyletic group separated from the H3N8 equine lineage [ 8 , 9 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Until earlier this year, the geographic distribution of H3N2 CIV had been limited to Asian regions, such as the Republic of Korea, China, and Thailand [ 10 , 12 17 , 19 , 20 ]; however, since the first outbreak in dogs in the USA in April 2015, it has rapidly spread to other Midwestern location from Chicago [ 22 , 23 ]. In contrast, H3N8 CIV has undergone a discontinuous distribution in three disjunctive continental areas: the USA [ 21 ] since 2004, Australia in 2007 [ 24 ], and the United Kingdom in 2002 [ 25 ]. Although the long-distance transmission of CIVs has occurred across continents and country boundaries in recent years, the transmission mechanism and reassortment events through space and time remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Equine-origin H3N8 and avian-origin H3N2 influenza viruses are capable of adaptation to canine populations and have established stable lineages in America, Europe, and Asia (4,(12)(13)(14)(15)(16). H3N8 CIVs have predominantly circulated in the United States since 2004 (2,17), and H3N2 CIVs are responsible for the bulk of infections in China and South Korea (4,18). Recently, it was determined that gene segment 3 of influenza A viruses encodes not only the polymerase acidic (PA) protein but also a novel protein, PA-X, that is translated as a ϩ1 frameshifted open reading frame (X-ORF) extension of the growing PA polypeptide (19,20).…”
mentioning
confidence: 99%